Recent Advances in Single-Atom Catalyst for Solar Energy Conversion: A Comprehensive Review and Future Outlook - Mehmood S.; Sk S.; Abraham B.M.; Ahmadipour M.; Pal U.; Dutta J. (John Wiley and Sons Inc, 2025)
Single-atom catalysts (SACs) are becoming increasingly recognized as highly promising catalytic materials, distinguished by their exceptional atomic efficiency, superior selectivity, and elevated activity levels. This review offers a detailed and comprehensive overview of the recent advancements in SACs, focusing on synthesis strategies, photocatalytic energy conversion applications, and advanced characterization techniques. Various synthetic approaches for fabricating atomically dispersed catalysts are elaborated concisely, emphasizing the importance of achieving precise atomic regulation on compatible supports to ensure strong metal?support interactions. Furthermore, the advanced characterization techniques by analytical tools are illustrated for a deep exploration of catalytic activity and mechanistic insights into uniformly dispersed SACs. Specifically, different kinds of support materials such as metal?organic frameworks (MOFs), their subset zeolitic imidazolate frameworks, and graphitic carbon nitride (g-C3N4) with diverse coordination and electronic environments are examined. Further, advances in computational techniques and machine learning are transforming SACs development by improving predictive accuracy and reducing trial-and-error methods, thereby accelerating the discovery of stable and active catalysts. Finally, current challenges and prospects of SACs based on MOFs, and g-C3N4 are addressed, providing valuable insights for the continued development and application of these catalysts in various industrial processes and environmental remediation efforts. ? 2024 The Author(s). Advanced Functional Materials published by Wiley-VCH GmbH.